Vitelyn Nylon-6 Plant - Cruz, Erlinda I. (College of Engineering, 1967)
This design project on nylon-6 covers the history of nylon-6, its physical properties and important uses, and its advantages over the other types of nylon. Actually, this project can be divided into two parts : the manufacture of e-caprolactam from cyclohexane; and the manufacture of nylon 6 from e-caprolactam. The final product is in the form of nylon filament. Also included in the contents of this book are the material and energy balance calculations, equipment specifications calculations, the results of which are further summarized. An estimate of the total fixed capital investment, the gross profit and other cost calculations can also be found in this book. As an over-all summary: Capacity: 10 tons of nylon-6 per 24-hour day -- Fixed capital investment: P 11,464,000 -- Operating cost at maximum production: P 5,668,696.80 -- Sales at maximum production: P10,640,000 -- Pay-out time: 2.0 years -- Break-even point: 19.2% or 1.92 tons/24 hr. day